2017
DOI: 10.6113/jpe.2017.17.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Non-equal DC link Voltages in a Cascaded H-Bridge with a Selective Harmonic Mitigation-PWM Technique Based on the Fundamental Switching Frequency

Abstract: In this paper, the Selective Harmonic Mitigation-PWM (SHM-PWM) method is used in single-phase and three-phase Cascaded H-Bridge (CHB) inverters in order to fulfill different power quality standards such as EN 50160, CIGRE WG 36-05, IEC 61000-3-6 and IEC 61000-2-12. Non-equal DC link voltages are used to increase the degrees of freedom for the proposed SHM-PWM technique. In addition, it will be shown that the obtained solutions become continuous and without sudden changes. As a result, the look-up tables can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In literature, several modulation schemes have been proposed for controlling the output voltage waveform quality of multilevel inverters. These can be listed as sinusoidal pulse width modulation (SPWM), space vector modulation, selective harmonic elimination (SHE)‐pulse width modulation (PWM), optimal minimization of THD (OMTHD), optimal PWM (OPWM), and selective harmonic mitigation‐(SHM) PWM . Out of these PWM schemes, SHE‐PWM scheme works on the low‐switching frequency, and it is used to completely eliminate (E‐1) number of specific low‐order harmonics of the output voltage using “E” number of switching instances in each quarter cycle of the output waveform.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In literature, several modulation schemes have been proposed for controlling the output voltage waveform quality of multilevel inverters. These can be listed as sinusoidal pulse width modulation (SPWM), space vector modulation, selective harmonic elimination (SHE)‐pulse width modulation (PWM), optimal minimization of THD (OMTHD), optimal PWM (OPWM), and selective harmonic mitigation‐(SHM) PWM . Out of these PWM schemes, SHE‐PWM scheme works on the low‐switching frequency, and it is used to completely eliminate (E‐1) number of specific low‐order harmonics of the output voltage using “E” number of switching instances in each quarter cycle of the output waveform.…”
Section: Introductionmentioning
confidence: 99%
“…In Najjar et al, an optimal SHM scheme has been suggested with equally variable DC voltage sources to satisfy some specified power quality standards for both three‐phase and single‐phase seven‐level CHB inverter over the entire modulation index range. Moeini et al introduces an efficient SHM scheme that satisfies standard grid code limits using four and 12 numbers of switching instances for three‐phase and single‐phase nine‐level CHB inverter, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations